(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article highlights the importance of incorporating audio and video lessons in teaching English to enhance listening skills, provide visual context, boost engagement, and offer flexibility in learning. By leveraging multimedia resources effectively, educators can create dynamic and interactive language lessons that cater to diverse learners and promote meaningful language acquisition. The use of audio and video materials not only enriches the learning experience but also equips students with the necessary skills to communicate confidently and effectively in English.